Production of Aspergillus niger GH1 tannase using solid-state fermentation - Cruz-Hernandez, M. A. (2009)
The production of tannase by Aspergillus niger GH1 in solid-state fermentation (SSF) was evaluated. Several concentrations of tannic acid (12.5, 25, 50 and 100 g/L) were tested in a model culture system. Column reactors were packed with polyurethane foam impregnated with liquid medium and inoculated with fungal spores. Tannase production was kinetically monitored by 48 h. Tannic acid uptake was spectrophotometrically measured and extracellular and intracellular tannase activities were assayed by HPLC-chromatography. Tannase activity increased with increasing concentration of tannic acid. Maximum extracellular and intracellular tannase activities (11.35 and 6.95 U/mL respectively) were recorded with 100 g/L of tannic acid. The substrate uptake was 100% at concentrations of 12.5, 25 and 50 g/L, while 74.4% was consumed in the presence of 100 g/L of tannic acid after 48 h of culture. These results suggest that high concentrations of tannins can be removed by SSF and tannase production can be reached in high levels.